STUDENTS’ IMPRESSION OF MIND MAPPING TECHNIQUE MIXED WITH FREEWRITING INFLUENCE THEIR WRITING ABILITY - Nurlaili Qurrotu Aini; Muhamad Sofian Hadi; Haznor Anis Aqilah Hazzaidi (STKIP Persada Khatulistiwa Sintang, 2023)
The aim of this research is to find out how students' impressions of the mind mapping technique mixed with freewriting influence their writing ability from Islamic Science University of Malaysia. One communication class was involved in this research with 15 students who take English for Communication subject. The survey research method was used in this research. Technique of collecting the data, the researcher used questionnaire. The results of this research revealed that students’ impressions of the mind mapping technique mixed with freewriting influence their writing ability is excellent. They can improve the writing ability using mind mapping technique mixed with freewriting. The validity and reliability used to test every statement in questionnaire with a significance level of 0.05 and the rtable is 0.514 from Pearson’s correlation coefficient. Most of respondents agreed with percentage 80% that their impressions as a student about mind mapping technique mixed with freewriting influence their writing ability is positive.